Identification of Non Performing Financing Alteration Measured by Microeconomic Variable Sharia Banking - Nihayah, Ana Zahrotun; Walyoto, Sri (Institut Agama Islam Negeri Surakarta, 2018)
This study analyzes the factors affecting Non-Performing Financing (NPF) in the sharia bank in Indonesia. The independent variable in this research uses microeconomic variables such as Capital Adequacy Ratio (CAR), Return on Assets (ROA), Financing to Deposit Ratio (FDR), Productive Financing Ratio (PFR), and Earning Asset Quality (EAQ). The sample used in this research is all population of Sharia Commercial Bank in Indonesia. The data used in this study were obtained from the Sharia Banking Statistics Report issued by the Financial Services Authority (Otoritas Jasa Keuangan - OJK) with the observation period from 2015 to 2017. The results showed that simultaneously CAR, ROA, FDR, PFR, and EAQ significantly influence NPF. Partially only variable FDR and EAQ which have the positive and significant influence to NPF, while CAR, ROA, and PFR has no significant effect on NPF.